The government-clerical language of Getmanschina (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article defines the role of language in the process of state creation, characterized by the language policy and features of functioning of the government-clerical language in Ukrainian Cossack Hetman state.
Keywords: language policy; language integration; government-clerical Ukrainian language